Organic Material Content In The Water Columnn And Sediment Of Coastal Water Of Sungai Bela District Indragiri Hilir - Prawira, Michael; Nurrachmi, Irvina; Nedi, Syahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in June 2015 in the waters of the Sungai Bela village Indragiri Hilir in the relationship of organic matter in the water column and sediment in the waters of the Sungai Bela village. Water samples were taken in the surface of the Sungai Bela using a sample bottle, sediment samples taken using Eickman grab of 16 sampling points. The content of organic matter in the water the highest at station 3 (35.19%) and the lowest for the Station 1 (19.44%). Organic matter the highest at station 3 is 28.20% and the lowest for the station 2 is 20.24%. Based on statistical test of the relationship of concentration of organic matter in water and sediment are strong relationships, or there is a positive relationship. The overall characteristics of the sediment fraction is dominated by silt fraction. Key words :Organik, Sedimen, Air, Sungai Bela